Design and Security Evaluation of an AES-256–Based Encrypted Receipt System for Electronic Service Businesses - M Syaifuddin; Moch. Iswan Perangin-angin (Journal of Information Systems and Technology Research, 2026)
The proliferation of digital technology has substantially heightened threats to customer data security within electronic service businesses at PT. Veneta. At present, PT. Veneta relies upon a manual transaction-recording system that remains vulnerable to theft, loss, and data deterioration. The absence of a computerized data-security infrastructure engenders significant vulnerabilities for potential misuse of customer data by unauthorized entities. In an effort to resolve these substantial challenges, a robust, efficient, and well-architected data-security system is requisite. The AES-256 algorithm represents one of the most formidable cryptographic algorithms for data protection, characterized by lightweight computational complexity. This algorithm demonstrates exceptional resistance to brute-force attacks and frequency-analysis methodologies. This research endeavors to design and implement a web-based customer data-security system utilizing the AES-256 algorithm at PT. Veneta. The research methodology employs Research and Development (R&D) utilizing a Waterfall approach encompassing six phases: requirements analysis, system design, development, testing, deployment, and implementation. The research findings demonstrate that the AES-256 algorithm successfully encrypts customer data into a 64-character hexadecimal ciphertext with exceptionally robust security characteristics. Unauthorized attempts to compromise the ciphertext via brute-force methodologies would necessitate 3.31 × 1056 years and 2256 key combinations. The data-security system implemented at PT. Veneta not only furnishes robust customer data protection but also substantially enhances customer confidence in data disclosure.